North Carolina Material Culture : An Analysis of the Excavation, Conservation, and Display of the Confederate Ironclad CSS Neuse - Caudill, Jessica (East Carolina University, 2013)
The CSS Neuse was a Confederate Ironclad stationed in Kinston, North Carolina. Today, it is one of a few surviving commissioned Confederate Ironclads, and is forgotten by many due to its lack of significant military history. While the ship does not have an extensive military background, its recent history is interesting and complex. This research is a multidisciplinary analysis of the ship's excavation, conservation, and display. The Neuse is a testament to the importance of cooperation between archaeologist, conservators, and museum professionals. During its original excavation, the ship sustained damage that affected the future conservation of the wooden hull. Also, since conservation was in its infancy during the time of the excavation, treatments were experimental. This research seeks to understand the full history and condition of the ship and associated artifacts in order to effectively preserve and display them for the future. Chemical analysis was employed to determine effectiveness of past treatments as well as levels of degradation, and recommendations were included regarding future conservation treatments. The Neuse is an important piece of North Carolina material culture, and an understanding of effective conservation is essential to the life and future display of the ship.
Keywords: History; Artifacts; Conservation; North Carolina; Neuse (Ship); Armored vessels--North Carolina; Underwater archaeology; North Carolina--History--19th century; North Carolina--History--20th century; North Carolina--History--Civil War, 1861-1865--Naval operations